Attentional Bias Towards Visual Itch and Pain Stimuli in Itch- and Pain-free Individuals? - Jennifer M. Becker; Sarah R. Vreijling; Sjoerd Dobbinga; Jolijn J.J. Giesbers; Andrea W.M. Evers; Dieuwke S. Veldhuijzen; Antoinette I.M. Laarhoven (Medical Journals Sweden, 2020)
Itch and pain are important attention-demanding sensations that allow adaptive responses to potential bodily harm. An attentional bias towards itch and pain stimuli, i.e. preferential attention allocation towards itch- and pain-related information, has been found in healthy, as well as patient groups. However, it remains unclear whether attentional bias for itch and pain differs from a general bias towards negative information. Therefore, this study investigated attentional bias towards itch and pain in 70 itch- and pain-free individuals. In an attention task, itch- and pain-related stimuli, as well as negative stimuli, were presented alongside neutral stimuli. The results did not indicate an attentional bias towards itch-, pain-, and negative visual information. This finding suggests that people without itch and pain symptoms do not prioritize itch- and pain-related information above neutral information. Future research should investigate whether attention towards itch- and pain-related information might be biased in patients with chronic itch and pain.